Segregated distribution of Liriope tetraphylla, Aglaura hemistoma and Nausithoe punctata (cnidaria) in the Southern Gulf of Mexico - Flores Coto, Cesar (2016)
In order to study the segregated distribution of the three most abundant jellyfish species in the southern Gulf of Mexico, a total of 85 stations were sampled during an oceanographic cruise from 19 May to 18 June 2006. Trawling took place from surface to a maximum depth of 200 m, using a Bongo net with a 61 cm mouth diameter and 333 and 500 µm mesh sizes. Temperature and salinity were recorded. Samples were preserved in 4% formalin, neutralized with sodium borate, and changed to 70% ethylic alcohol after 24 hours for conservation. The jellyfish data were standardized to 100 m3 of filtered water. A total of 10,610 jellyfish were collected from the 333 µm mesh size net, of which eight species represented 88.49% of the total density: Aglaura hemistoma, Liriope tetraphylla, Nausithoe punctata, Clytia hemisphaerica, Persa incolorata, Obelia spp., Clytia folleata and Eutima gracilis. The former three species are the subject of this study. The results obtained indicate that the high density areas of these three species have a segregated distribution. Segregation values (White’s index) recorded between pairs of specie were very high: L. tetraphylla - A. hemistoma, 0.88; L. tetraphylla - N. punctata, 0.86 and A. hemistoma - N. punctata, 0.84. The spatial distribution of the high density areas of these species fits well with the three hydrodynamically different areas: A. hemistoma in Campeche Bank, L. tetraphylla on the Campeche and Tabasco shelves and N. punctata in Campeche Bay. This spatial distribution pattern corresponds to their main habitat and reproductive habits of the species, as well as the influence of the hydrodynamics that dominate each area.